Avaliação da toxicidade e determinação das atividades biológicas dos flavonóides vitexina, tilirosídeo e 5,7-dihidroxi-3,8,4'-trimetoxi: estudos in silico, in vitro e ex-vivo - Sousa, Aleson Pereira de (2022)
Complementary therapies using medicinal plants and herbal medicines are quite common in Brazil. Among several Brazilian plant species used in such therapies, the species of the Malvaceae family stand out. The present study aimed to investigate the bioavailability, toxicity, solar protection factor and determination of the antimicrobial and genotoxic potential of the flavonoids vitexin, tiliroside and 5,7-dihydroxy-3,8,4'-trimethoxy (Pg-1), isolated from species of the Malvaceae family, using in silico, in vitro and ex vivo studies. The chemical structure and predicted bioactive properties were analyzed in silico using software. The in vitro and ex-vivo assays using human samples were performed in accordance to the Ethics Code of the World Medical Association and were approved by the Ethics Committee (protocol number: 3.621.284). The in silico analysis of the chemical structure of the molecules and the expected bioactive properties shows that vitexin and Pg 1 have oral bioavailability and good absorption owing to their balanced lipophilicity/hydrosolubility, while tiliroside has increased lipophilicity resulting in increased permeability of biological membranes. The in silico toxicity tests revealed the potential efficacy of these molecules in cellular protection against free radicals, in addition to possible antimutagenic, anticarcinogenic, antioxidant, antineoplastic, anti-inflammatory, anti-hemorrhagic and apoptosis agonist activity. The in vitro cytotoxic and ex-vivo genotoxic evaluation detected low rates of hemolysis in human red blood cells and no cellular toxicity against oral mucosa cells. The reduction in cytotoxic activity is indicative of the safety of the concentrations used (500-1000 µg/mL) and demonstrates different forms of interaction of the molecules with the types of cells analyzed. The MIC showed a strong effect of the flavonoids vitexin, tiliroside and Pg-1 against K. pneumoniae, E. coli and E. fecalis. The MBC revealed that vitexin has a bacteriostatic effect for strains of K. pneumoniae and E. fecalis, tiliroside had a bactericidal effect against a strain of K. pneumoniae, Pg-1 was considered bactericidal for strains of E. fecalis and E. coli, and bacteriostatic in the K. pneumoniae strain. The data suggest that vitexin, tiliroside and Pg-1 are safe molecules for possible therapeutic applications and their toxicity profile indicates that they are promising targets for future studies.